2014
DOI: 10.1039/c4dt01581a
|View full text |Cite
|
Sign up to set email alerts
|

How big is a Cp? Novel cycloheptatrienyl zirconium complexes with tri-, tetra- and pentasubstituted cyclopentadienyl ligands

Abstract: The new bulky cyclopentadienyl anions 1,2,4-tri(cyclopentyl)cyclopentadienide and 2,3-diisopropyl-1,4-dimethyl-5-trimethylsilyl-cyclopentadienide were prepared. These and the already known 1,2,4-tri(cyclohexyl)-, 1,2,4-tri(isopropyl)-, 2,3-diisopropyl-1,4-dimethyl-, 1,3,4-triisopropyl-2,5-dimethyl-, pentaphenyl-, and p-butylphenyl-tetraphenyl-cyclopentadienide as well as tert-butylindenide were coordinated to the cycloheptatrienylzirconium fragment [(CHT)ZrCl(tmeda)]. The nine zirconium complexes of the [(CHT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Steric bulk has been quantified extensively for phosphine ligands using the approach initially developed by Tolman . Inspired by the TCA definition for dissymmetrically substituted phosphines, we adapted the formalism to substituted Cp X ligands (Figure A) . Accordingly, angles α i between the vector defined by the Rh–Cp­(centroid) axis, and the vectors tangential to the outermost atomic sphere of each substituent R i are measured in DFT-optimized structures (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Steric bulk has been quantified extensively for phosphine ligands using the approach initially developed by Tolman . Inspired by the TCA definition for dissymmetrically substituted phosphines, we adapted the formalism to substituted Cp X ligands (Figure A) . Accordingly, angles α i between the vector defined by the Rh–Cp­(centroid) axis, and the vectors tangential to the outermost atomic sphere of each substituent R i are measured in DFT-optimized structures (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, an ensemble of quantitative molecular descriptors is usually required to account for all of the subtleties of chemical structure. Moreover, the steric and electronic components of these parameters cannot be completely decoupled from one another, except in rare cases. ,, Recently, stepwise linear regression algorithms found widespread utility in handling the typically large number of parameters involved in multivariate free energy relationships. ,, …”
Section: Resultsmentioning
confidence: 99%
“…In a series of cycloheptatrienyl zirconium complexes featuring substituted Cp ligands, Walter and co-workers previously found increasing steric demand in the order Cp″ (1,3-( t Bu) 2 C 5 H 3 ) < Cp* < Cp ttt (1,2,4-( t Bu) 3 C 5 H 2 ) < Cp iPr4 < Cp iPr5 . With the first reported structures containing the (Cp iPr4 ) 2 U moiety in hand, we were interested in whether these steric differences among Cp ligands might also manifest in similar trends in the corresponding Cp­(cent)–U–Cp­(cent) angles.…”
Section: Resultsmentioning
confidence: 94%
“…63,64 A comparison of 2-X with their 3-X analogs reveals expected bond lengthening upon reduction from uranium(IV) to uranium(III). 65 In a series of cycloheptatrienyl zirconium complexes featuring substituted Cp ligands, Walter and co-workers previously found increasing steric demand in the order Cp″ (1,3- 72 With the first reported structures containing the (Cp iPr4 ) 2 U moiety in hand, we were interested in whether these steric differences among Cp ligands might also manifest in similar trends in the corresponding Cp(cent)−U−Cp(cent) angles. We found that similar Cp(cent)−U−Cp(cent) angles occur between 2-Cl (142.97(7)°) and 2-F (146.53(6) in 2-F and 141.63(5)°(avg.)…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Since the discovery of ferrocene, Cp 2 Fe, organometallic chemistry has been dominated by the cyclopentadienyl (Cp) ligand; a large number of cyclopentadienyl complexes with tailored steric and electronic properties have been developed [1][2][3][4][5] for various applications ranging from material science and small molecule activation to (enantioselective) catalysis. In contrast, the chemistry of the "open" analogues, the pentadienyl ( pdl) ligands, and their corresponding metal complexes has received significantly less attention and the investigations have mainly focused on d-transition metals, [6][7][8][9][10] whereas complexes of the rare earth, [11][12][13][14][15][16][17][18][19][20][21] actinide [21][22][23][24][25] and main group metals [26][27][28][29][30][31][32][33][34][35][36][37][38] have been surprisingly scarce.…”
Section: Introductionmentioning
confidence: 99%